The TRUST Study-TRansition US Together: Evaluating the Impact of a Parent- and Adolescent-Centered Transition Toolkit on Transition Readiness in Patients with Juvenile Idiopathic Arthritis and Childhood-Onset Systemic Lupus Erythematosus - Simran Heera; Karen Beattie; Zubin Punthakee; Briano DiRezze; Julie Herrington; Tania Cellucci; Liane Heale; Mark Matsos; Jan Willem Gorter; Michelle Batthish (MDPI AG, 2024)
Objective: Adolescents with chronic rheumatic disease must increasingly take on more responsibility for disease management from parents as they transition from pediatric to adult care. Yet, there are limited resources to inform and support parents about transition. Here, we evaluate the impact of a Transition Toolkit, geared towards parents and adolescents, on transition readiness, and explore the potential impact of parent-adolescent communication. Methods: A prospective cohort study of youths aged 14-18 years old and their parents was performed. Participant demographics, disease characteristics, transition readiness scores (Transition-Q, max 100), and parent-adolescent communication scores (PACS, max 100) were collected at enrollment (when the Transition Toolkit was shared with adolescents and their parents. Generalized estimating equation (GEE) analyses determined the influence of the Toolkit on transition readiness and explored the role of parent-adolescent communication quality. Subgroup analyses were conducted by sex. Results: A total of 21 patients were included; 19 completed one post-intervention Transition-Q and 16 completed two. Transition-Q scores increased over time and the rate of increase doubled after the Toolkit was shared (β = 7.8, p < 0.05, and β = 15.5, p < 0.05, respectively). Conclusion: Transition readiness improved at each follow-up, the greatest increase was seen after the Toolkit was shared. Parent-adolescent communication quality did not appear to impact changes in transition readiness.